Exploring the benefits of a psychomotor intervention mediated by creative dance in community-dwelling older adults: development of new coordination and rhythm tests - Hugo Rosado; Patrícia Motta; Gabriela Almeida; Ana Cruz-Ferreira; Catarina Pereira (BMC Public Health)
Abstract Background Psychomotor intervention mediated by creative dance is emerging as an enjoyable practice that stimulates balance, coordination, and rhythm, benefiting physical function, cognition, and overall health in older adults. Despite the relevance of this practice, validated tests for assessing motor coordination and rhythm in older adults—essential parameters for motor control and movement regulation—are still needed. Thus, this study assessed the effects of a psychomotor intervention using creative dance in global motor coordination, rhythm, and balance in community dwellings. For this intent, one test to assess older adults' global motor coordination and one test to assess rhythm were developed and tested. Methods This 12-week non-randomized clinical trial study included 38 participants (73.4 ± 5.7 years), allocated into two groups. The experimental group (EG; n = 19) attended the psychomotor intervention (3x/week; 50 min/session), while the control group (CG; n = 19) maintained their daily activities. Previous, global motor coordination and rhythm tests were developed based on the underlying literature and expert consultation. Their reliability and validity were determined. Fullerton Advances Balance Secale assessed Balance. Results The test’s intra and inter-rater reliability was excellent, ranging 0.962–1.00. There were positive correlations between the test variables and theoretically-related parameters, p < 0.05. Within-group comparison revealed significant improvements after the intervention in the EG global motor coordination, rhythm, and balance, p < 0.05. Significant differences between groups concerning change (pre-post-intervention) in the previous variables were found, p < 0.05, with an effect size ranging 0.40–0.74. Conclusions The current study supports the reliability and validity of the developed global motor coordination and rhythm tests in community dwellings. Nonetheless, further research is recommended to substantiate these findings in men. The psychomotor intervention mediated by creative dance induced large beneficial effects in global motor coordination, rhythm, and balance. These findings suggest that this practice is beneficial for promoting community-dwelling older adults’ healthy aging. Trial registration ClinicalTrials.gov Identifier: NCT04311931. Date of registration: March 17, 2020.